Dopaminergic therapy disrupts decision‐making in impulsive‐compulsive Parkinsonian patients - Fabio Taddeini; Erica Ordali; Alessandra Govoni; Francesca Piattellini; Simone Valente; Luca Caremani; Alberto A Vergani; Ahmet Kaymak; Aldo Rustichini; Eleonora Russo; Chiara Rapallini; Silvia Ramat; et al. (Annals of Clinical and Translational Neurology)
Abstract Impulsive‐compulsive behaviors (ICB) are common non‐motor symptoms of Parkinson's disease (PD) often associated with dopaminergic drugs (DD) therapy. We investigated the acute effects of DD on decision‐making in PD patients with ICB (ICB+) and without it (ICB−), and in healthy controls (HC). Participants performed a risk‐based decision‐making task twice, with PD patients tested before (DD OFF) and after (DD ON) DD intake. In DD OFF, all groups developed a risk‐averting strategy. In DD ON, ICB+ patients (but not ICB− nor HC) reverted to riskier choices. We conclude that DD has a specific strong acute effect on ICB+ patients' decision‐making.